Potential of Salivary Matrix Metalloproteinase 9 to Discriminate Periodontal health and disease - Atarchi, Ahmed R (Journal of Baghdad College of Dentistry, 2022)
Periodontitis is a chronic inflammatory disease resulted from aggravated immune response to a dysbiotic subgingival microbiota of a susceptible host. Consequences of periodontitis are not only limited to the devastating effect on the oral cavity but extends to affect general health of the individual and also exerts economic burdens on the health systems worldwide. Despite these serious outcomes of periodontitis; however, they are avoidable by early diagnosis with proper preventive measures or non-invasive interventions at earlier stages of the disease. Clinically, diagnosis of periodontitis could be overlooked due to certain limitations of the conventional diagnostic methods such as periodontal charting and radiographs. Utilization of readily available biomarkers in the oral biofluids represents a potential opportunity to overcome these issues. This topic received great attention in the last decades and one of these biomarkers is matrix metalloproteinase 9 which is highlighted in this review as one of the candidates that can be used for diagnosis of periodontal diseases